E-business—Trends and Issues - Guda, Neerja (Indian Journal of Marketing, 2005)
The internet has brought about a dramatic change in the ways businesses are done in today's world. It is seen that one of the important issues being faced by organizations around the world is how to build an effective e-business strategy and the relevant technology choices involved thereof. It is pertinent to note in this context that it is not technology alone but how one uses the technology to transform the business processes. In fact one of the key parameters companies are being evaluated for their marketing efficiency is how well they can adapt themselves to the internet and exploit the advantages of the e-business.